The immunogenicity and reactogenicity of the trivalent vaccine, Trimovax, indicated for prevention of measles, mumps, and rubella, in 12-month-old children in Belarus - Samoilovich, E O; Kapustik, L A; Feldman, E V; Yermolovich, M A; Svirchevskaya, A J; Zakharenko, D F; Fletcher, M A; Titov, L P (Central European journal of public health, 2000)
In the Republic of Belarus, immunization of children against measles and mumps had been carried out using monovalent preparations according to the national schedule of measles vaccination at 12 months of age and mumps vaccination at 24 months of age. A rise of rubella incidence in the last few years (i.e., for the official registration period 1980 to 1998, there was an increase from 72.2 to 607.5 cases per 100,000 population) made it necessary to implement immunization against this infection, as well. Therefore, in 1996, combined vaccination against measles, mumps, and rubella of 12-month-old children was carried out for the first time in a clinical trial that used the vaccine Trimovax [Aventis Pasteur (formerly, Pasteur Mérieux Connaught), Lyon, France]. The reactogenicity of the vaccine was investigated in 372 children. Post-vaccination reactions were noted in 5.6% of children; in 1.3% of children the reactions were classified as severe [i.e. associated with body (axillary) temperature > or = 38.6 degrees C]. For the evaluation of immunogenicity, sera from 324 children were obtained 2 to 2.5 months after inoculation, and serum antibody levels were measured by enzyme immunoassays. Among the vaccines, protective antibody titers (expressed in inverse of dilution units) were observed to measles (> or = 1:50) in 97.8%, to mumps (> or = 1:50) in 93.8%, and to rubella (> or = 1:100) in 96.0% of children. Antibodies to all three components of the vaccine were mainly present in intermediate (1:200-1:800) or high (> or = 1:1600) titers: to measles in 96.3%; to mumps in 75.8%; and to rubella in 73.5% of vaccines. The results of these trials are evidence of the good safety and immunogenicity of this MMR vaccine, which provides an alternative to the currently used measles and mumps monovaccines, with the additional benefit of providing immunity against rubella, as well.
Keywords: Běloruská republika; zarděnky; Mumps; protilátky virové; Rubella; Measles; Antibodies, Viral; Measles-Mumps-Rubella Vaccine; Infant; Humans; vakcína proti spalničkám, příušnicím a zarděnkám; příušnice; lidé; Republic of Belarus; kojenec; spalničky